Faktor-Faktor Penyebab dan Kendala-Kendala yang dihadapi dalam Pemberian Bantuan Hukum Nonlitigasi Penyuluhan Hukum Lembaga Bantuan Hukum Kepada Kelompok Orang Miskin di Kota Kupang - Ibrani Arianto Dite; Rudepel Petrus Leo; Bhisa Vitus Wilhelmus (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
study aims to find out and analyze the factors that cause legal aid institutions to not be verified as legal aid institutions to the poor and the obstacles faced by legal aid institutions in providing non-litigation legal aid in the form of legal counseling to the poor obtained through interviews and observations and empirical juridical, namely those obtained through interviews and literature research. The results of the study show: (1) the factors that cause legal aid institutions to not be verified as legal aid institutions to the poor include: legal factors, law enforcement officials, infrastructure factors, community factors and cultural factors (2) obstacles faced by legal aid institutions in providing non-litigation legal assistance in the form of legal counseling to the poor, which include: internal factors and external factors.